An Exploration of Discursive Framings of Body Weight in Obesity Canada and the Association for Size Diversity and Health’s Websites - Waugh, Rachel (Cuizine, 2025)
Body weight discourse varies based on which researcher you speak to. This can be confusing for those new to the field of weight science, especially for students or early career researchers. Organizations like Obesity Canada have student-led “Student and New Professional” groups which discuss higher-weights as “obesity” with students in healthcare related fields. Medicalizing body weight and labelling obesity as a chronic disease differs from Health At Every Size® or the work that fat studies scholars are doing. This can create turmoil for students, unsure of where they fit in these discussions of weight. This research paper was completed as part of an undergraduate directed study to explore discourse as a method to analyze body weight paradigms. First, discourse is explored as a method, then the medicalization of body weight is questioned. Viewpoints like those of Obesity Canada, Health At Every Size®, and fat studies scholars are explored and compared. A discourse analysis was completed to compare and contrast Obesity Canada and the Association of Size Diversity and Health’s websites. Findings indicate fatness can be framed differently, dependant on positionality (e.g., healthist or sizeist) and ideologies present on online websites.